Monitoring vibrations and microdisplacement for "pin on disc" tribology studies - Tyurin, A E; Ismailov, G M; Beloenko, E V; Baranov, A V (Journal of physics. Conference series, 2017)
The paper studies the example of applying accelerometers to evaluate tribocoupling vibration characteristics and verification methods in the testing system "pin on disc". Microelectromechanical systems (MEMS) intended for operation over a wide static and spectral ranges were applied. Accelerator spatial track recovery was implemented through the double integration algorithm. In the course of the work, the vibrations occurring through the friction between fluorocarbon and brass alloy LS59-1 under the conditions of dry friction were studied.